Sistem Federal Dalam Negara Kesatuan (Kasus Pengaturan Desentralisasi-Otonomi) - Utomo, Warsito (Jurnal Ilmu Sosial dan Ilmu Politik, 1998)
In fact, unitary state and federal state system has similarity in the reladon between nation orpusat and states or daerah, emphasizing in power sharing, negotiation and distribution of income. New federalism shows how the states have more authority than the dual federalism and cooperative federalism. The applied of federal system as in the new federalism (a model that represents a return of powers and responsibilities to the state/daerah) will solve the conflict and dichotomies whether the desire as the unitary state (Negara Kesatuan) or developing federal state (Negara Federal) is still in the consideration.